Burying the Ghosts of a Complainant’s Sexual Past: The Constitutional Debates Surrounding Section 227 of the Criminal Procedure Act 51 of 1977 - Omar, Jameelah (Department of Public Law, 2015)
“It has been said that the victim of a sexual assault is actually assaulted twice- once by the offender and once by the criminal justice system.”1 South Africa’s rape shield provision is contained in section 227 of the Criminal Procedure Act.2 The purpose of its enactment is to protect a complainant in a sexual offence matter from secondary victimisation during the trial as far as possible, by restricting the type of evidence that is admissible and the circumstances under which such evidence can be found to be admissible. This rationale has come under attack for its effect on the fair trial rights of the accused. There has been no challenge to the constitutionality of section 227 before a court yet. However, there are numerous rumblings of discontent at the consequences of a provision that restricts evidence that could be necessary to prevent a wrongful conviction. This paper seeks to consider the constitutional debates surrounding section 227 and to determine whether, to the extent that they may prove to be constitutionally problematic, the potential constitutional challenges are justifiable under a limitations analysis. It is impossible to engage with the constitutionality of section 227 without first discussing the rationale behind rape shield laws in general. The structure of the paper is therefore as follows: firstly, the history and purpose of rape shield laws will be investigated, and secondly, the history of section 227 under South African law will be discussed.